2015
DOI: 10.1016/j.jfineco.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Technology spillovers and corporate cash holdings

Abstract: This study examines the effect of technology spillovers on firms' cash holdings. It finds that firms facing greater technology spillovers hold higher cash balances. This effect is more pronounced among financially constrained firms and for firms that are likely to benefit more from diffused technology, e.g., those have newer patents, are more profitable, face better growth opportunities and are associated with greater product market fluidity. The spillover impact remains strong when product market competition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(62 citation statements)
references
References 56 publications
5
57
0
Order By: Relevance
“…The holding of cash also gives firms a competitive edge in their pursuit to either outperform their rivals in securing larger market shares (Bolton and Scharfstein (1990), undertaking new investment opportunities (Haushalter et al (2007), or winning technological races (Qiu and Wan (2015). In all such cases, holding more cash relative to rivals gives a firm strategic advantage, which can boost its market value.…”
Section: Corporate Governance and The Propensity Of Managers To Spendmentioning
confidence: 99%
“…The holding of cash also gives firms a competitive edge in their pursuit to either outperform their rivals in securing larger market shares (Bolton and Scharfstein (1990), undertaking new investment opportunities (Haushalter et al (2007), or winning technological races (Qiu and Wan (2015). In all such cases, holding more cash relative to rivals gives a firm strategic advantage, which can boost its market value.…”
Section: Corporate Governance and The Propensity Of Managers To Spendmentioning
confidence: 99%
“…To avoid the effects of collinearity, we did not add an annual dummy variable in the regression. Based on the assumptions in this paper, we expect the estimated coefficient of 3  to be significantly negative, that is to say, during the period of monetary policy tightening, listed companies with high default risk have more cash holdings. Equation (2) is the debt term structure equation, the dependent variable is the debt maturity structure (Ld), and the cash holdings are the endogenous control variables determined jointly with the dependent variable.…”
Section: Definition Of Main Variablesmentioning
confidence: 97%
“…"Cautious Motivation" believes that holding cash in the company can prevent possible risk shocks, which will be more intense when external financing costs are higher. Qiu & Wan (2015) found that adequate cash holdings helped the company compete in technology and innovation, and technology spillovers were significantly positively correlated with cash holdings. Therefore, when the company faces fluctuating cash flow, it can use precautionary cash holdings to buffer the debt repayment risk and ensure the company's subsequent investment capacity.…”
Section: Analysis Of the Mechanism Of Debt Holdings Affecting Cash Homentioning
confidence: 99%
“…Like Grossman and Helpman (1991), Griliches (1979), Jaffe, Trajtenberg, and Henderson (1993), Almeida, Campello, and Weisbach (2004), Han and Qiu (2007), Jiaping and Chi (2015) test the impact of technology on companies liquidity. The authors presented their research hypotheses according to which a positive impact of technology on cash holdings is assumed.…”
Section: The Literature Reviewmentioning
confidence: 99%